A new approach to prepare nano hydroxyapatite from oyster shells used for dental applications - Kifayah Aljaberi; Rafid M. AlBadr; Kareema M. Ziadan (Journal of Kufa-Physics, 2022)
HA (hydroxyapatite) is considered one of the biomaterials widely, it is applied in many applications like medical and dentistry. In this research, NHA powder was prepared from some natural source rich in calcium carbonate, it was prepared by calcination method at 1200 ℃ for 2 hours. The samples were diagnosed by using various diagnostic tests including scanning electron microscopy (SEM (, X-ray diffraction (XRD), Fourier transform infrared (FTIR), X-ray spectroscopy (EDX), and density measurements. The XRD results showed that HA as-prepared high purity and the crystallite size as around 63.561± 11.327 nm, while the particle sizes≈ 63 nm according to BET, also EDX clearly showed elements (Ca, P, O). As for the density of NHA, it was measured and found to be equal to (2.98±0.1) g/cm3. Characterization results (XRD, SEM, EDX, FTIR, and BET) showed the morphological and structural properties of the Hydroxyapatite.